Agroecological assessment and efficiency of potential fertility - Nagornykh Alexander; Dolgopolova Natalya; Philimonov Pavel; Eremenko Olga (BIO Web of Conferences, 2024)
The paper raises the issues of biosphere development, which is carried out against the background of complex processes of substance and energy exchange. Under the influence of V.I. Based on Vernadsky's ideas, major progress was made in studying the movement of chemical elements and redistribution of matter within different parts of the biosphere. The energy of soil formation is a new scientific direction, studying on the basis of system analysis the regularities of transformation of solar energy spent on soil formation (physical and chemical destruction of soil-forming rocks, hyper gene transformation of minerals, etc.), revealing objective ecological conditions of formation and distribution of soils and biogeocenosis in the biosphere. An important task of soil formation energy is the development of effective technological systems to increase the full utilization of solar energy, to create highly productive natural and agricultural biocenoses. Before outlining the main directions of soil formation energetics, it is necessary to define a set of issues that are relevant to this problem. They should include sources and expenditures of energy in soil formation, the amount of energy accumulated in the soil, and others. Much less attention is paid to the energy assessment of these processes. Meanwhile, cognition of the regularities of energy exchange and transformation in the biosphere is a very important problem of modern natural science. From the energy point of view, the emergence and development of the biosphere on Earth should be considered as a grandiose process of gradual accumulation of the stock of convertible solar energy in the surface layer of the planet.